Yusuf Azeem is not a hero - Faruqi, Saadia (Quill Tree Books, an imprint of HarperCollinsPublishers, 2021)
"Yusuf is excited to start middle school in his small Texas town, but with the twentieth anniversary of the September 11 attacks coming up, suddenly it feels like the country's same anger and grief is all focused on his Muslim community"--